High thermal conductive shape-stabilized phase change materials of polyethylene glycol/boron nitride@chitosan composites for thermal energy storage. (February 2020) - Jia, Xiwen; Li, Qingye; Ao, Chenghong; Hu, Rui; Xia, Tian; Xue, Zhouhang; Wang, Qunhao; Deng, Xueyong; Zhang, Wei; Lu, Canhui
Abstract: Phase change materials (PCMs) applied in the energy storage and temperature control system are crucial for energy conservation and environmental protection. In this work, boron nitride (BN)@chitosan (CS) scaffolds with three-dimensional (3D) porous structures were fabricated. And effective thermal conductive pathways could be created in the resultant scaffolds. By introducing polyethylene glycol (PEG) into the BN@CS scaffolds, composite PCMs with large latent heat of fusion and excellent shape-stability were obtained. In particular, a high thermal conductivity up to 2.77 W m −1 K −1 could be reached at a relatively low content of BN (27 wt%). Moreover, they also exhibited a satisfactory energy storage density of 136 J g −1 . This work demonstrated a facile and environmentally friendly strategy to simultaneously achieve enhancement of thermal conductivity, high energy storage density, shape stability and outstanding thermal repeatability for composite PCMs, which held promising potential in waste heat recovery, cooling system and temperature control system.